A noise impact assessment model for passive acoustic measurements of seabed gas fluxes. (1st July 2019) - Li, Jianghui; White, Paul R.; Bull, Jonathan M.; Leighton, Timothy G.
Abstract: Accurate determination of seabed gas flux is important for understanding natural processes as well as giving confidence that the size of any leaks from marine infrastructure can be properly assessed. Acoustic methods for flux determination require a relatively quiet underwater environment, and can fail when there is too much noise from other natural or anthropogenic sources. This study applies an acoustic monitoring example of seabed gas leakage in terms of sound level intensity, to statistically assess and minimize the impact from oceanic noise on seabed acoustic experiments which require a relative quiet environment. It addresses the question: how far from a source of radiated ambient noise does a recording hydrophone and location of seabed gas need to be so that acoustic methods for remotely determining gas flux are successful. We develop a model to assess impacts of ambient noise under various conditions, incorporating sound/noise sources (seabed gas leaks, sea surface agitation and shipping) and underwater acoustic propagation. The reliability of the model is tested by comparing measured seabed ambient noise in the central North Sea, and the robustness of it is verified by presenting statistical outliers and a receiver operating characteristic (ROC) curve. A range of scenarios are presented for several gas flow rates, which show the threshold of detection when the recording hydrophone is at different distances from the location of seabed gas escape, and competing noise sources (including shipping and surface waves).